Waktu Optimum Biokonversi Spontan Biji Asam Guna Meningkatkan Kandungan Nilai Gizinya Sebagai Pakan Ternak Alternatif (OPTIMUM TIME OF SPONTANEOUS FERMENTATION TO NUTRIENT VALUE OF TAMARIND SEED AS ALTERNATIF FEED) - Wea, Redempta; Koni, Theresia Nur Indah; Sabuna, Cytske (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
The aim of this research is to evaluate nutrition value and optimum time of spontaneous bioconversionof tamarind seed. This research was conducted using complete random design experimental methodswith five bioconversion time treatments ie R0 0 hour; R1 24 hours; R2 48 hours; R3 72 hours; and R4 96hours respectively and each treatment consist of four replications. The data were then analysis usingvariants analysis and Duncan’s test. The research variable was nutrition value of tamarind seed spontaneousbioconversion. Results showed that spontaneous bioconvertion was not effecting to dry matter, crude fiber,and crude fat but effected to ash, crude protein, and metabolism energy and the best treatment wasspontaneous bio-conversion until 72 hours and make decreasing at 96 hours treatment Based on thoseresult, for getting the best result,it is suggesting to use spontaneous bioconversion until 72 hours.
Keywords: spontaneous bioconvertion, tamarind seed, nutrition value